Idiopathic Giant Hepatic Artery Pseudoaneurysm - Ahmed Abdelbaki; Neeraj Bhatt; Nishant Gupta; Shuo Li; Shady Abdelbaki; Yogesh Kumar (Case Reports in Vascular Medicine)
Hepatic artery pseudoaneurysm (HAP) incidence is rising due to more common use of endoscopic and percutaneous hepatic interventions. HAP is potentially fatal, as it could lead to sudden life-threatening hemorrhage. HAP can be intrahepatic or extrahepatic. On computed tomography angiogram (CTA) and magnetic resonance angiogram (MRA), HAP follows blood pool on multiphasic examination, with brisk arterial enhancement that washes out, similar to the abdominal aorta on later phases. We present a case of idiopathic giant HAP in an 82-year-old male. Currently, angioembolization is replacing surgery as the initial modality of choice for management of this condition.